Immunomodulatory properties of polysaccharide extract samples from Cyanobacterium sp. Rippka B-1200 - Stanislav Sukhikh; Vladimir Popov; Egor Kashinskikh; Ekaterina Budenkova; Svetlana Ivanova; Olga Babich (Scientific Reports)
Abstract Cyanobacteria are most abundant in aquatic systems and can grow in freshwater, saline or brackish water, and cold/hot springs. Cyanobacteria have attracted considerable research attention in the last decade as a potential source of numerous biological products in large quantities, such as biofuels, pigments, polyunsaturated fatty acids, nutraceuticals, enzymes, and polysaccharides. Unlike most plant and fungal polysaccharides, the chemical composition, immunomodulatory activity, and molecular mechanisms of action of Cyanobacterium sp. Rippka B-1200 polysaccharides have been studied much less. The complexity of their primary structure due to the high variability of monosaccharides, their diverse bonds, the presence of substituents and high viscosity made detailed structural studies of cyanobacterial polysaccharides rare, which determines the need for analysis of cyanobacteria biomass components to identify active metabolites with promising biological activity. The aim of this study was to investigate the immunomodulatory properties of polysaccharides from Cyanobacterium sp. Rippka B-1200. Pharmacological and nutraceutical value of Cyanobacterium sp. Rippka B-1200 has been set, defining our study’s scientific novelty. As a result, the molecular weight of immunoactive polysaccharide (6.0–8.0 kDa) was determined. The analysis shows that endopolysaccharide samples at a concentration of 300 mg/kg showed no significant immunomodulatory effect (1.60 ± 0.15 mg/g), and the thymus mass index of animals in the experimental group was comparable to that of the control group in which animals were immunosuppressed with cyclophosphamide (1.15 ± 0.24 mg/g). When exopolysaccharide samples were used at a concentration of 600 mg/kg, the thymus mass index of animals in the experimental group (3.60 ± 0.32 mg/g) was statistically comparable to that of the control group (without polysaccharide) in which immunosuppression was not induced (thymus index was 3.70 ± 0.25 mg/g). It was found that endopolysaccharide samples at a concentration of 600 mg/kg also exhibited high immunomodulatory activity. When Cyanobacterium sp. Rippka B-1200 endopolysaccharide samples were used, no internal organ changes were observed in experimental animals after immunosuppression. The empirical results presented in the study may find application in the development of both pharmaceutical and cosmetic products.